KAJIAN HUKUM TERHADAP RISIKO EKSPLORASI DAN EKSPLOITASI MINYAK DAN GAS BUMI - Budi Handojo (Sekolah Tinggi Maritim Yogyakarta, 2017)
Normative legal research toward the risks of exploration and exploitation of oil and natural gas is a response to environmental disasters of lapindo mudflow in porong, Sidoarjo,, East Java. In an effort to find solutions of problems occurred, namely environmental damage and losses that occur as a direct result of mining activities of PT. Lapindo Brantas has caused great losses, both public property and citizens. Who must take the responsibility for whatever risks that may happened based on the Petroleum Natural Gas Act and the Environmental Management Act ? Based on analysis of data it can be delivered the following results, (1) According to the prevailing laws and regulations the rights of state control over oil and gas held by the government as the authority of Mining, which in the implementation of authority is carried out by the oil and Gas Implementing Body. Thus Enterprises of PT. Lapindo Brantas which conducts the exploration and exploitation in Porong’s mining area, Sidoarjo has to get the concession based on the Cooperation Contract. (2) Concerning to the environmental damages and losses occurred as the results of mining activities of PT. Lapindo Brantas, the company is obliged to take responsibility for whatever risks that may happened. Similarly, the state should not escape from the consequences as the authority of mining which has the obligation to protect the interests and general welfare, in any attempt to use the natural resources for prosperity of the people as great as possible.